Strategic Management of Strengthening Character Education through Learning at Madrasyah Aliya Negeri Tangerang Selatan City - Sutarman Sutarman; Ariesta Setyawati; Silvia Hanifa; Ica Risdheani; Cici Aprianti (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this research is to understand the strategic management of strengthening education through character learning through online and offline learning which includes planning, implementation, and evaluation. The research method uses a qualitative approach through interviews, observations, and documentation studies at Madrasah Aliyah Negeri Tangerang Selatan. Analysis with data reduction, data display, verification, and conclusions. The results of the study are: (1). Planning through preparation, and policy mapping, according to procedures and stages of learning (2). Organizing forms a team as the head of the principal, the daily leader of the vice principal, and teachers to carry out character education through online and offline learning (3). Implementation of character education is carried out through learning activities, exemplary, priority scale, reflection, coaching, habituation of student discipline through religious activities, nationalism, social care, and environmental care (4). Evaluation of the implementation of online and offline learning in Madrasah Aliyah Negeri Tangerang Selatan. With supervision, precise and objective assessment of the accuracy of tasks, cooperation, and effective and efficient achievement of online and offline learning.